Hubungan Proses Pembelajaran Menulis Proposal Terhadap Hasil Kemampuan Menulis Proposal Mahasiswa - Putri Roganda Pane; Shelomita A.P Komaling; Melani Limbong; Surya Yusuf; Roihan Nasution; Yopita Sidabutar; Malan Lubis (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
This research aims to analyze the relationship between the learning process to write proposals and the results of students' proposal writing abilities. This research uses quantitative methods with a correlational approach. Data was collected through observation, questionnaires and document analysis from a sample of students taking the proposal writing course. The research results show that there is a significant relationship between the quality of the proposal writing learning process and students' proposal writing abilities. Factors such as teaching methods, teaching materials, and the level of student involvement in the learning process contribute positively to improving proposal writing skills. The implications of this research indicate that improving the quality of the learning process can improve the results of students' proposal writing abilities, which in turn can support their academic and professional success.